2021
DOI: 10.18502/ijph.v50i5.6123
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Tumor Necrosis Factor-Alpha and Neuropeptide Y Expression and Neurological Function Score in Epileptic Children

Abstract: Background: To observe the relationship between Tumor Necrosis Factor-alpha (TNF-α) and Neuropeptide Y (NPY) expression and neurological function score in epileptic children. Methods: Fifty-four epileptic children diagnosed and treated in Xuzhou Children's Hospital, China from Feb 2017 to Mar 2018 were collected and included in a research group (RG), while 30 healthy children who underwent physical examination at the same time were included in the control group (CG). ELISA was used to detect the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The above studies all suggest that NPY plays an important function in neurodegenerative diseases. A recent Chinese study showed that the level of NPY in peripheral blood of epileptic children was significantly increased and was positively correlated with NIHSS score and Hamilton Anxiety (HAMA) scores, suggesting that NPY is involved in the onset of epilepsy [ 23 ]. A study by Peking University showed that plasma NPY is significantly reduced in Vasovagal Syncope, which may participate in the pathogenesis of Vasovagal Syncope by increasing total peripheral vascular resistance and reducing cardiac output [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above studies all suggest that NPY plays an important function in neurodegenerative diseases. A recent Chinese study showed that the level of NPY in peripheral blood of epileptic children was significantly increased and was positively correlated with NIHSS score and Hamilton Anxiety (HAMA) scores, suggesting that NPY is involved in the onset of epilepsy [ 23 ]. A study by Peking University showed that plasma NPY is significantly reduced in Vasovagal Syncope, which may participate in the pathogenesis of Vasovagal Syncope by increasing total peripheral vascular resistance and reducing cardiac output [ 24 ].…”
Section: Discussionmentioning
confidence: 99%